An In Vitro comparative assessment of shaping capacity of a single-File system over multiple-file system in root canals - Bollineni Swetha; Duvvuri L Malini; Devipriya Burla; Prabu Mahin Syed Ismail; Surya Dahiya; Ritasha Bhasin; Azhar Mohammed (Wolters Kluwer Medknow Publications, 2024)
Objectives: The study's objective was to contrast the two distinct rotary file techniques used to shape mandibular first molars. Materials and Methods: The investigation involved twenty recently removed mandibular molars. A digital single-lens reflex (DSLR) camera was placed in a fixed position, a muffle block was built, and images of each tooth's three cross sections were obtained. The specimens were split into the following two groups at random: Rotary files from WaveOne were used to prepare group A and Mtwo rotary files were used to prepare group B. Results: At the coronal, middle, and apical thirds of the root canals, WaveOne file system demonstrated improved centering ability compared with the Mtwo file system (P 0.05). Conclusion: When compared to the Mtwo file system, WaveOne file system demonstrated improved centering capabilities and needed significantly less time to build the curved canals.